THE CORRELATION OF PD-L1 EXPRESSION IN CYTOLOGICAL AND HISTOLOGICAL MATERIAL OF SEROUS HIGH-GRADE OVARIAN CANCER - Jovanović, Ljubiša; Ćirković, Anđa; Nikolić, Ljubinka; Jović, Milena; Mikić, Darko; Milenković, Svetlana; Janković, Radmila (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Neoplastic cells in peritoneal lavage express various proteins with significant prognostic and therapeutic potential. Such expression could differ from the expression in a primary tumor or in metastases. In this research, we compared PD-L1 (programmed cell death ligand-1) expression on ovarian cancer cells in cytological material with its expression on peritoneal metastases and a primary tumor. Materials and methods: The study included 30 patients who had been operated on for high-grade serous ovarian cancer (HGSC) in FIGO IIIC, over the period of one year. Cytoblocks, cytological and tissue microarrays were assembled and immunostained with PD-L1 antibody. For each tumor compartment we determined four PD-L1 expression categories: negative, low, moderate, and strong expression, according to the percentage of membrane positive tumor cells. Moderate and strong positivity together were considered as high PD-L1 expression. Results: Moderate PD-L1 expression was the most frequent pattern in primary HGSC (50%) and in peritoneal metastases (omentum) (60%). Cytological samples mostly showed low PD-L1 expression (57%). Statistical analysis did not show a significant difference in PD-L1 expression between the study groups. We found a positive correlation of PD-L1 expression between different, matched tumor samples in every patient, with statistical significance (p<0.05) between all the analyzed samples. Conclusion: PD-L1 expression was similar in all three tumor compartments. This could point to similar peritumor regulatory mechanisms of HGSC in primary tumor tissue and cytology tumor samples. Immunohistochemical analysis of the assembled cytoblocks is sufficiently reliable in the assessment of PD-L1 expression on cancer ovarian cells from cytological material.